Epidemiology in trafic accidents - Elena Ciuchilan; Tatiana Iov; Liviu Pendefunda (Romanian Neurosurgery, 2011)
The industrialization and the technological advance we can affort more and more, allowed the car numbers increasing and the car accident as well. The paper presents the victim number status of Neamţ area for the period of 2005-2008, split on sex and type of participant in accident. The aim is to help out the local authorities with information, more precisely the police, in order to improve the car trafic safety by getting specific measures.